Isomorphic Mimicry and Social Inclusion: an Analysis of the Capability of Wonosobo District Government in Implementing the Inclusive Education Policy - Fernandito Dikky Marsetyo; Nurhadi Nurhadi (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
This article examines the implementation of the inclusive education policy to provide educational services for children with disabilities. Using a conceptual framework concerning disability and social inclusion, and isomorphic mimicry and capability, this article aims to explain Wonosobo District Government's capability in implementing inclusive education policy. This article is based on a qualitative study, using a case study approach with descriptive analysis. We argue that Wonosobo District Government's capability to implement inclusive education policy is in a weak or limited position (weak capability). This is a depiction of isomorphic mimicry, where the inclusive education policy in Wonosobo District seems to be functional. As its implication, children with disabilities are vulnerable to being excluded from obtaining inclusive education services.